INNOVATIVE DEVELOPMENTS IN THE FIELD OF INTELLECTUAL AND INFORMATION TECHNOLOGIES AND INNOVATIONS IN METHODS OF FORECASTING BUSINESS PROCESSES BASED ON THEIR SOFTWARE IMPLEMENTATION (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
This article will focus on innovative developments in the field of intellectual and information technologies and methods of forecasting business processes based on their software implementation. Innovations in their forecasting methods and neural networks are also revealed. Solving the problems of economic analysis at the enterprise is a factor that ensures the competitiveness of any organization at every stage of its development. This article reveals the main features of the application of data mining methods in forecasting the activities of an enterprise, and also provides a list of typical tasks and algorithms used in their solution.
Keywords: business processes